Advances in the therapeutic application and pharmacological properties of kinsenoside against inflammation and oxidative stress-induced disorders - Lu, Li; Xiong, Yuan; Lin, Ze; Chu, Xiangyu; Panayi, Adriana C.; Hu, Yiqiang; Zhou, Juan; Mi, Bobin; Liu, Guohui (Frontiers in Pharmacology, 2022)
Considerable documentations have verified that inflammation and oxidative stress are intimately implicated in the development of multiple diseases, such as diabetes, hepatitis and arthritis. Kinsenoside (KD), a bioactive glycoside component extracted from medicinal plant Anoectochilus roxburghii, has been proved to exhibit potent anti-inflammatory and anti-oxidative abilities. In this review, we summarize the pleiotropic pharmacological effects of KD and observed that the hepatoprotection, pro-osteogenesis, anti-hyperglycemia, vascular protection, immune regulation, vision protection and infection inhibition actions of this phytochemical are partly attributed to suppressing inflammation signaling and oxidative stress. Moreover, there is a possibility that protective mechanisms of KD against dysfunction of lipid metabolism are associated with impeding the inflammatory signals, due to the crosstalk between inflammation pathways and lipid metabolic cascades. Ferroptosis, involved in inflammatory and oxidative damage processes, is likely to be a potential target regulated by KD to exert curative effects. In addition, physicochemical properties and pharmacokinetic profiles of KD are discussed, which show that cultivation technique advancement and artificial synthesis improvement are promising to overcome the shortage of raw materials responsible for producing this botanic derivative and drug delivery systems are possible to improve the rapid clearance and poor bioavailability of KD in vivo. We anticipate that the information contained in this integrated review will offer novel insights into the molecular mechanisms underlying the therapeutic roles of KD and lay solid foundations for the utilization of KD as a potential candidate in clinical practice.